2014
DOI: 10.1007/s00420-014-0963-4
|View full text |Cite
|
Sign up to set email alerts
|

Does rare use of assistive devices during patient handling increase the risk of low back pain? A prospective cohort study among female healthcare workers

Abstract: The study indicates that rare use of assistive devices can increase the risk for developing infrequent LBP in female healthcare workers reporting to be free from LBP at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Technical patient handling aids, also known as mechanical assistive devices, can reduce the number of manual patient lifts required. The resulting decrease in lifting forces experienced by health care workers during patient handling can help to prevent complaints and disorders due to overloading [ 31 , 32 , 33 , 34 ]. Therefore, the German Social Accident Insurance Institution for the Health and Welfare Service (Berufsgenossenschaft für Gesundheitsdienst und Wohlfahrtspflege (BGW)) [ 35 ] recommends the use of patient lifting devices to prevent physical workload while handling patients.…”
Section: Introductionmentioning
confidence: 99%
“…Technical patient handling aids, also known as mechanical assistive devices, can reduce the number of manual patient lifts required. The resulting decrease in lifting forces experienced by health care workers during patient handling can help to prevent complaints and disorders due to overloading [ 31 , 32 , 33 , 34 ]. Therefore, the German Social Accident Insurance Institution for the Health and Welfare Service (Berufsgenossenschaft für Gesundheitsdienst und Wohlfahrtspflege (BGW)) [ 35 ] recommends the use of patient lifting devices to prevent physical workload while handling patients.…”
Section: Introductionmentioning
confidence: 99%
“…In general, however, a reduction in lost workdays due to injury was also found with ergonomic programme implementation [15,16,18,51], as were reductions in injury-related costs [16,51]. The quality of the study evidence overall is not high; some are small [13,14,41], not randomised [4,16,42,46,49,52], or lacking appropriate controls [4,12,16,17,45,49,50], or include other factors which may have an influence on the study result [44,48,51]. Table 1.…”
Section: In Relation To Healthcare Workers: Ergonomic Devices And/or mentioning
confidence: 96%
“…The number of lost workdays due to injury was also generally reduced with introduction of ergonomic devices [7,43,45], as were costs associated with patient handling-related injury [45]. Use of ergonomic devices was also associated with reduced awkward back posture incidence and duration [46], safer patient transfers [47], and reduced risk of infrequent lower back pain [48]. Burdorf et al reported, however, that even the best scenario only showed a maximal reduction of 14% in lower back pain prevalence, while the projection from this analysis was that complete elimination of manual patient lifting would reduce lower back pain by 10.5% [43].…”
Section: In Relation To Healthcare Workers: Ergonomic Devices And/or mentioning
confidence: 99%
See 1 more Smart Citation
“…Following this, some of the most promising interventions aiming to reduce the physical load among healthcare workers seem to be the ones focusing on decreasing the frequency and/or intensity of manual lifting [25][26][27][28][29]. This is often and most successfully done by increasing the use of assistive devices during patient transfers, as previous studies have reported associations between frequent use and lower risk of back injury and MSDs [30][31][32]. However, it is currently unknown whether this effect is mainly due to single/specific assistive devices or if it is related to the consistent use of a combination of assistive devices.…”
mentioning
confidence: 99%